Improving Students’ Sundanese Language Skills through the Implementation of Video Media and Wordwall Games at Al Ghazaly Elementary School - Badriyyah , Nurul; Asmahasanah, Salati (ATTA`DIB, 2025)
Sundanese as one of the Language area own role important in preservation culture local. Currently​ existence Sundanese language, facing quite a challenge Serious consequence existence domination Language foreign in activity daily activities that impact the number of Sundanese speakers from circles generation increasingly young​ decreased. The minimum the use of Sundanese in life daily specifically for students who live in the area urban, as well as use method lack of learning interesting in learning Sundanese causes low interest student in learn Sundanese so that the ability Sundanese language owned by students Still limited. Research this aim for increase ability Sundanese speaking students Grade IV of Al Ghazaly Elementary School through application of learning media interactive in the form of videos and wordwall games. This research use study action research method Kemmis and Mc Taggart model. This research results show existence improvement in every aspect ability Sundanese language students at the end cycle that reaches figure ≥ 75%, besides that activity students and teachers in activity learning also experiences significant improvement. With​ thus, it can concluded that video media and wordwall games are proven can increase ability Sundanese speaking students.